019. Idiopathic interstitial pneumonias: clinico-radiologic-pathologic diagnosis - Baliaka, Aggeliki (J Thorac Dis, 2015)
BACKGROUND: The idiopathic interstitial pneumonias (IIPs) represent a heterogeneous group of lung diseases with effects on the lung parenchyma and airways characterized by chronic inflammation and progressive fibrosis and share similar features (clinical, radiological). The idiopathic interstitial pneumonias are classified based on clinical, histopathological and radiological criteria in idiopathic pulmonary fibrosis-usual interstitial pneumonia (IPF-UIP), nonspecific interstitial pneumonia (NSIP), cryptogenic organizing pneumonia (COP), desquamative interstitial pneumonia (DIP), acute interstitial pneumonia (AIP), respiratory bronchiolitis-associated interstitial lung disease (RB-ILD) and lymphocytic interstitial pneumonia (LIP). OBJECTIVE: The importance of clinical-imaging-pathology findings correlation for the final diagnosis of two cases with idiopathic interstitial pneumonia. METHODS: 1(st) case: 68-year-old male with dyspnea and interstitial thickening in the lower lobe of the left lung and radiologic characteristics of peripheral atelectasis and pulmonary fibrosis-CT guided lung biopsy. 2(nd) case: 56-year-old male with dyspnea and honeycomb changes in the lower lobe of the right lung-Partial lobectomy, 5, 8×5×2 cm(3) in size, was performed. RESULTS: In both cases a variety of histopathological changes was noticed, such as: diffuse alveolar damage with confluent alveolar septal thickening; fibrosis with fibroblastic foci, smooth muscle hyperplasia and foci of ossification (2(nd)); dilated airspaces; bronchiolar or squamous metaplasia of alveolar epithelium; inflammation in the interstitium; dilated and congested blood vessels. The valuation of histological findings in accordance with history, clinical and imaging findings confirmed the diagnosis of usual interstitial pneumonia (UIP). CONCLUSIONS: The diagnosis of idiopathic interstitial pneumonias is the result of collaboration between pulmonologists, radiologists and pathologists. The subtypes are important to distinguish because treatment and prognosis vary by subtype and ranges from excellent to nearly always fatal. The reasons of interstitial lung fibrotic lesions identification failure are: incomplete clinical information, inadequate radiological data, small or non-diagnostic biopsy sample, previous treatment which differentiates the clinical picture or histology and heterogeneity of histological changes from site to site.